2021
DOI: 10.1038/s41929-021-00625-x
|View full text |Cite
|
Sign up to set email alerts
|

Following the structure of copper-zinc-alumina across the pressure gap in carbon dioxide hydrogenation

Abstract: Copper-zinc-alumina catalysts are the industrially-used formulation for methanol synthesis from carbon monoxide and carbon dioxide containing feedstock. Its high performance stems from synergies that develop between its components. This important catalytic system has been investigated with a myriad of approaches, however, no comprehensive agreement has emerged as to the fundamental source of its high activity. One potential source of the disagreements is the considerable variation in pressure used in studies t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
180
1
16

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 155 publications
(206 citation statements)
references
References 64 publications
9
180
1
16
Order By: Relevance
“…At pressures of 5 bar and above, the reduction occurs at 423 K [29] . Figure 1a and b show the development of Zn K‐edge XANES and non‐phase corrected Fourier transformed (FT) EXAFS observed during in situ temperature‐programmed reduction (TPR) of the CZA catalyst under 10 bar of hydrogen up to 800 K [29] . Similar plots for the other pressures studied can be found in Supplementary Figure S1.…”
Section: Resultsmentioning
confidence: 63%
See 4 more Smart Citations
“…At pressures of 5 bar and above, the reduction occurs at 423 K [29] . Figure 1a and b show the development of Zn K‐edge XANES and non‐phase corrected Fourier transformed (FT) EXAFS observed during in situ temperature‐programmed reduction (TPR) of the CZA catalyst under 10 bar of hydrogen up to 800 K [29] . Similar plots for the other pressures studied can be found in Supplementary Figure S1.…”
Section: Resultsmentioning
confidence: 63%
“…The evolution of the Cu K‐edge XANES and its interpretation in terms of transformation of the copper phase measured in the same experiment can be found in ref. [29]. It was found that the reduction of Cu II to metallic copper in hydrogen is a strong function of pressure.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations